Native Participation in Land Management Planning in Alaska - Gallagher, Thomas J. (ARCTIC, 1988)
Land ownership and land management in Alaska have changed dramatically since 1980. Native people have become owners of relatively small tracts of private land surrounded by large federal and state holdings. These public lands are the responsibility of a variety of agencies, each of which is preparing land management plans to guide how the land is to be used. Native people, to protect their traditional use of the land, must participate successfully in the preparation of these plans. Four problems inhibit participation: (1) native people are overloaded by the large number of plans, (2) the "world view" of native cultures does not readily accept planning, (3) the public meeting used by all agencies is an inappropriate forum for native participation, and (4) differences in communication style complicate discussion between native people and non-native planners. Potential solutions include coordinating planning efforts to reduce the number of plans, use of more appropriate participation methods, and training of non-native planners in cross-cultural communication and native people in land management planning.Key words: land planning, land management, native people, public participation, cross-cultural communication Mots clés: planification du territoire, gestion du territoire, autochtones, participation publique, communication inter-culturelle